2013
DOI: 10.1159/000332811
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of the Guanylyl Cyclase-Cyclic GMP-Protein Kinase G Pathway to the Proliferation of Neural Stem Cells Stimulated by Nitric Oxide

Abstract: Nitric oxide (NO) is an important inflammatory mediator involved in the initial boost in the proliferation of neural stem cells following brain injury. However, the mechanisms underlying the proliferative effect of NO are still unclear. The aim of this work was to investigate whether cyclic GMP (cGMP) and the cGMP-dependent kinase (PKG) are involved in the proliferative effect triggered by NO in neural stem cells. For this purpose, cultures of neural stem cells isolated from the mouse subventricular zone (SVZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Moreover, direct activation of sGC with YC-1, and, thus, increasing in cGMP production, also enhances NSC proliferation upon 24 h of treatment. Likewise, a cGMP analogue, 8-Br-cGMP, also enhances SVZ cell proliferation, as shown in this work and previously by our group [9]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, direct activation of sGC with YC-1, and, thus, increasing in cGMP production, also enhances NSC proliferation upon 24 h of treatment. Likewise, a cGMP analogue, 8-Br-cGMP, also enhances SVZ cell proliferation, as shown in this work and previously by our group [9]. …”
Section: Discussionsupporting
confidence: 88%
“…We also show that ERK1/2 is activated following treatment with PDE5 inhibitors (except sildenafil), suggesting the involvement of this pathway in cell proliferation mediated by PDE5 inhibition. Taken together, our data point out to the activation by PDE5 inhibition in SVZ cells of two pathways: the sGC/PKG and the ERK/MAPK pathways, the same pathways responsible for the proliferative effect of NO [9]. …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The proliferative effects of cGMP in SVZ NSCs have been attributed to activation of PKG-dependent pathways [66]. A recent study also suggested a role of cGMP during brain development in vivo by demonstrating that rats in which cGMP levels had been reduced during embryonic development showed reduced differentiation of stem cells to neurons in the cortex and in the DG of the hippocampus [21].…”
Section: Discussionmentioning
confidence: 99%